Characteristics of Snack Bar "Banaris" from Fortified Non Cereal Flour as Emergency Food for Toddler. (September 2019) - Rachmat, R; Hastuti, W; Darniadi, S
Abstract: The objective of the research is the development of banaris bar products using flour-based of local food with FIR technology, that fulfill the economic, social-cultural, nutritional and health eligibility requirements as an alternative food emergency to support diversification national food because this product is needed in accordance with the adequacy of nutrients for the age group of nutrient-prone (infants and toddlers). fortification, testing product characteristics, packaging, shelf life testing, probiotic testing of Bifidobacterium sp and Lactobacillus sp and testing of serum retinol concentrations in children under five year. The effect of giving Banaris bar products gives positive results on increasing subject height. The provision of Banaris bar products containing prebiotics can stimulate the growth of the Lactobacillus sp population in the toddler's digestive tract in the treatment group compared to the control group toddlers.. The level of crispness, elasticity, stickiness, compactness and fragility of the banaris bar is lower than the regular bar snack. The packaging used is aluminum foil primary packaging and secondary packaging, namely carton. The packaging consists of 3 variants, namely packaging for six pieces with a size of 10.5 x 8 x 3.5 cm, packing for 9 pieces with a size of 15 x 8 x 3.5 cm and packaging for 15 pieces with a size of 15 x 13 x 3.5 cm. Banaris bar products have a shelf life of 10 months.